Diindolocarbazole – achieving multiresonant thermally activated delayed fluorescence without the need for acceptor units. Issue 3 (24th January 2022) - Hall, David; Stavrou, Kleitos; Duda, Eimantas; Danos, Andrew; Bagnich, Sergey; Warriner, Stuart; Slawin, Alexandra M. Z.; Beljonne, David; Köhler, Anna; Monkman, Andrew; Olivier, Yoann; Zysman-Colman, Eli
Abstract : We present a new multi-resonance thermally activated delayed fluorescence (MR-TADF) emitter paradigm, demonstrating that the structure need not require the presence of acceptor atoms. Abstract : In this work we present a new multi-resonance thermally activated delayed fluorescence (MR-TADF) emitter paradigm, demonstrating that the structure need not require the presence of acceptor atoms. Based on an in silico design, the compound DiICzMes4 possesses a red-shifted emission, enhanced photoluminescence quantum yield, and smaller singlet-triplet energy gap, Δ E ST, than the parent indolocarbazole that induces MR-TADF properties. Coupled cluster calculations accurately predict the magnitude of the Δ E ST when the optimized singlet and triplet geometries are used. Slow yet optically detectable reverse intersystem crossing contributes to low efficiency in organic light-emitting diodes using DiICzMes4 as the emitter. However, when used as a terminal emitter in combination with a TADF assistant dopant within a hyperfluorescence device architecture, maximum external quantum efficiencies of up to 16.5% were achieved at CIE (0.15, 0.11). This represents one of the bluest hyperfluorescent devices reported to date. Simultaneously, recognising that MR-TADF emitters do not require acceptor atoms reveals an unexplored frontier in materials design, where yet greater performance may yet be discovered.